THE AFFIRMATION OF SELF-EXISTENCE IN “LADY OF SCANDAL’’ BY TINA GABRIELL - Tomi Arianto; Noviana Osinta Bere (eScience Humanity Journal, 2020)
This study aimed to analyse the affirmation of self-existence against patriarchal construction in the novel "Lady of Scandal" by Tina Gabrielle. This research used feminist approach Simone de Beauvoir (2016) in her theory women existence. This study focused on four factors that caused women against patriarchy, namely submissive, matchmaking, mala fide and domesticity. To analyse kinds of affirmation against patriarchal construction, researcher focused on the Beauvoir terminology related; the intellectual, being herself, and freedom to actualize self. This research used qualitative methods. In this study, the researcher found on two points that made woman against patriarchy. First, because women have seen as second sex who were oppressed by men based the values and norms by society who believed in patriarchal culture. Second, woman awareness against patriarchy reflected from the showing of her existences as a woman